Development of a new product for unrestrained heart rate measurement in swimming: a user centered design approach - van Rooijen, V.; de Voogd-Claessen, L.; Lauche, K.; Jeanne, V.; van der Vliet, R. (Procedia Engineering, 2010)
This paper reports the development of a new product for unrestrained heart rate measurement to provide feedback and target training efforts in professional swimming. While training is considered to be the key to becoming a top athlete, little is known about how to determine the right training course for individual athletes (Maase, 2009, ). In order to optimize the training load of an individual athlete, coaches need to monitor physiological indicators that are linked to performance.Interviews with the Dutch Olympic swimming team have shown that coaches feel the need for ways "to be able to look inside the athlete's body" (Wouda, 2009) and get insight in their capacities without restraining them. In swimming coaches use VO2 levels, heart rate, lap times and lactate to adapt the training load. However measuring VO2 levels and lactate is too invasive and expensive for regular use. This makes heart rate a suitable measure.For land sport, there are several devices on the market that measure heart rate at appropriate costs, however these are not suitable for professional swimmers. Interviews with coaches of the Dutch Olympic team have shown that anything that increases the resistance of the body will not be acceptable for swimmers. Existing products were deemed inappropriate because they restrict the athlete's movement, tend to shift in the water during jumps or turns or are not accurate. Therefore current heart rate monitors are not used on top level and coaches rely only on lap times as direct feedback of the training load during regular trainings. This might lead to under training or over reaching.A new product designed to measure a swimmers heart rate without using inconvenient sensors is being developed within Philips Research. Heart rate is measured through analysis of visual signs in between laps and direct feedback is given to the swimmer and coach during the training. The measurement data is not only shown during training, but is also stored for later analysis. This paper will report that development from a user-centred design perspective. The design focuses on the special needs of top athletes represented by the national swimming training centre in Eindhoven, The Netherlands. The use of this new product will enable unobtrusive measurement with direct feedback to optimise the individual training load and push athletes to the limit.